Perencanaan Syariah - Muslim Kamil (Faculty of Economic and Business, 2014)
Any individual or any organization definitely requires planning in a variety of activities. Good planning is not based on sharia, or Islamic-based (conventional) basically has a lot in common, in addition to also have many differences. In this article the author intends to explain the concept - the basic concept of sharia perenaaan well as its association with the concept of conventional planning. Thing - the most important thing in this article is a discussion about the basic concepts, principles, vision, mission, the laws, the feasibility and planning stages in sharia Planning sharia is essentially the same as planning in general, the difference principle is the 'value - value' that surrounded him. Because it takes a lot of socialization and continuing on the planning concept of sharia.DOI: 10.15408/ess.v4i3.2435